FIBER ORIENTATION IN METAL INJECTION MOLDED SHORT CARBON FIBER REINFORCED COPPER MATRIX COMPOSITE - SHIRAZI, MUHAMMAD IRFAN (2014)
Short carbon fiber (CF) reinforced metal matrix composites (MMCs) are a favorable candidate for aerospace and electronics industries. Improving short fiber orientation can significantly enhance physical and mechanical properties of these MMCs. Powder Injection molding (PIM) has the potential to control orientation of short fibers in MMCs. This research was focused to develop carbon fiber reinforced copper composite feedstocks with three component binder system using a z-blade mixer. Fluw properties of copper and composite feedstocks were determined using a capillary rheometer. A specially designed mold was used to enhance fiber orientation in molded samples. Binder was removed by solvent and thermal techniques at 60°C and 500°C respectively. Debound test samples of copper and copper/CF composites were sintered at 1050°C for 3 hours for densification.